FAKTOR YANG MEMPENGARUHI KEPATUHAN PERAWATAN ULKUS KAKI DIABETIK BERULANG - Fatmawati; Supriadi; Puspita, Dinarwulan (Literasi Intelektual, 2024)
Background: Diabetic foot ulcers (DFU) are among the most common complications in patients with type 2 diabetes mellitus. One of the key factors influencing ulcer healing is patient compliance. Adherence to treatment is essential for diabetic patients, especially those with infected wounds. Objective: To determine the factors associated with patient compliance in the management of recurrent diabetic foot ulcers. Methods: This study employed a quantitative analytic design with a cross-sectional approach. The study population consisted of 140 patients with recurrent diabetic foot ulcers, and a total of 58 respondents were selected using purposive sampling. Data were analyzed using the Chi-square test with a 95% confidence level (α = 0.05). Results: The findings revealed a significant relationship between knowledge (p = 0.002), healthcare facility support (p = 0.001), healthcare worker support (p = 0.037), and family support (p = 0.011) with the level of patient compliance in recurrent diabetic foot ulcer care. Conclusion: There is a significant association between knowledge, healthcare facility support, healthcare worker support, and family support with patient compliance in the management of recurrent diabetic foot ulcers.